Advancements in Host-Based Interventions for Influenza Treatment - Yip, Tsz-Fung; Selim, Aisha Sami Mohammed; Lian, Ida; Lee, Suki Man-Yan (Frontiers in Immunology, 2018)
Influenza is a major acute respiratory infection that causes mortality and morbidity worldwide. Two classes of conventional antivirals, M2 ion channel blockers and neuraminidase inhibitors, are mainstays in managing influenza disease to lessen symptoms while minimalizing hospitalization and death in patients with severe influenza. However, the development of viral resistance to both drug classes has become a major public health concern. Vaccines are prophylaxis mainstays but are limited in efficacy due to the difficulty in matching predicted dominant viral strains to circulating strains. As such, other potential interventions are being explored. Since viruses rely on host cellular functions to replicate, recent therapeutic developments focus on targeting host factors involved in virus replication. Besides controlling virus replication, virus-induced host immune response, such as the latest ideas suggesting the involvement of innate lymphoid cells and NADPH oxidases in influenza virus pathogenesis as well as the renewed interest in immune cell metabolism may serve as potential targets for drug development. In this review, we will discuss the advancements in novel host-based interventions for treating influenza disease.